The Influence of Different Characteristic Demographics of Beef Cattle Farmers on Adoption of Concentrate and UMMB Technology - Sutrisno Hadi Purnomo; Rendi Fathoni Hadi; Sulistyo Sulistyo (International Journal of Agriculture System, 2018)
This research aimed to find out the influence of different demographic characteristics of beef cattle farmers on adoption of concentrate and UMMB (Urea Mineral Molasses Block) technology. The method employed was a descriptive quantitative with survey technique conducted on beef cattle farmers. The sample was selected using convenience sampling method, with 65 beef cattle farmers as the sample. The primary data was obtained from questionnaire and interview with 65 beef cattle farmers. The secondary data was obtained from Karanganyar Regency’s Central Statistic Agency. The data analysis employed included descriptive analysis, validity, reliability, and Oneway ANOVA tests. The results showed that the different demographic characteristics of beef cattle farmers (age, education, main job, job duration, breeding business status and cattle number owned) influence the adoption of concentrate and UMMB technology. The conclusion of research was that the demographic characteristics of beef cattle farmers showed different effects on the adoption of concentrate and UMMB technology.